Assessing Groundwater Level and Water Quality in Bhaktapur Municipality: A Pre-Monsoon and Post-Monsoon Analysis - Mandal, Rohinee Bishwas; Shakya, Shreeben; Ghale, Bimala; Lakhe, Hanik; Duwal, Sudeep; Shakya, Bijay (Khwopa Journal, 2023)
Groundwater is a crucial natural resource for sustaining human life, agriculture, and ecosystems worldwide. In many Asian countries, including Nepal, groundwater has emerged as a dependable source of water, particularly in areas where surface water is scarce or unreliable. For instance, in Bhaktapur Municipality (BM), Nepal, groundwater has been contributing around 50–60% of the total water supply. However, over the past few years, extensive extraction, alterations in the land use pattern, and other anthropogenic interventions have posed serious threats to this highly valuable resource. As such, groundwater monitoring is an essential primary step for understanding the status of the groundwater resource. Meanwhile, the Water Quality Index (WQI) is an effective tool that can turn complex water quality data into simplified information that is understandable and usable by the public. This study aimed to understand the groundwater levels and further comprehend the groundwater quality using the WQI of the BM. The groundwater level data and water samples were collected from 24 spatially distributed wells of the BM in the post-monsoon of 2021 and the pre- and post-monsoon of 2022. Laboratory analysis was carried out to determine the nine physico-chemical water quality parameters, and the obtained parametric values were compared with those of the World Health Organization (WHO) and the National Drinking Water Quality Standard (NDWQS). The results show deeper groundwater levels in the core area than the periphery, and the water quality getting poorer from post-monsoon 2021 to post-monsoon 2022. The EC, TDS, pH, phosphate, chloride, and hardness of most of the samples were within the permissible limits of WHO and NDWQS, whereas the turbidity, ammonia, and alkalinity of many samples exceeded the permissible limits. Average WQI revealed that the majority of the samples were unsuitable for drinking and suitable only for household and irrigation purposes. This study provides insights into managing water demands, addressing issues of water scarcity, and highlighting the urgent need for additional research and policymaking to improve drinking water quality and the sustainability of groundwater management in BM.